Stepping up during a crisis: The unintended effects of a noncontributory pension program during the Covid-19 pandemic - Nicolas L. Bottan; Bridget Hoffmann; Diego Alejandro Vera Cossío (Inter-American Development Bank (IDB), 2020)
This paper uses a regression discontinuity design to study the impacts of a noncontributory pension program covering one-third of Bolivian households during the COVID-19 pandemic. Although the program was not designed to provide emergency assistance, it took on additional importance during the crisis, providing unintended positive impacts. Becoming eligible for the program during the crisis increased by 25 percent the probability that households had a week's worth of food stocked and decreased the probability of going hungry by 40 percent. Relative to the pre-pandemic years, the program's effect on hunger is magnified during the crisis. The program's effects were particularly large for households that lost their livelihoods during the crisis and for low-income households. The results suggest that, during a systemic crisis, a preexisting near-universal pension program can quickly deliver positive impacts in line with the primary goals of a social safety net composed of an income-targeted cash transfer and an unemployment insurance program.
Keywords: H55; H84; I15; I38; 330; Cash transfers; Resilience; Social insurance; COVID-19; Noncontributory pensions